Nanotechnological exploitation of the antioxidant potential of Humulus lupulus L. extract. (1st November 2022) - Lela, Ludovica; Ponticelli, Maria; Caddeo, Carla; Vassallo, Antonio; Ostuni, Angela; Sinisgalli, Chiara; Faraone, Immacolata; Santoro, Valentina; De Tommasi, Nunziatina; Milella, Luigi
Graphical abstract: Abstract: The present study investigated the potential antioxidant applications of Humulus lupulus L. as raw extract and nanoformulated in liposomes. H. lupulus is commonly used as a food ingredient, but it is also a promising source of specialized metabolites with health-promoting effects. In the extract obtained by hydroalcoholic maceration, 24 compounds were characterized using liquid chromatography-mass spectrometry analyses. The extract exhibited an interesting antioxidant activity in in vitro spectrophotometric and cell assays. The extract was nanoformulated into liposomes to exploit and improve its beneficial proprieties. The in vitro assays revealed that, after incorporation into liposomes, the extract's antioxidant activity was preserved and even improved. Moreover, a lower dose of the extract was required to prevent reactive oxygen species overproduction when included in the nanoformulation. These results confirm the advantages of nanoformulating herbal extract to maximize its health-promoting effects for a potential pharmaceutical application.